2003
DOI: 10.1161/01.res.0000066663.12256.b2
|View full text |Cite
|
Sign up to set email alerts
|

Functional Roles of the Rho/Rho Kinase Pathway and Protein Kinase C in the Regulation of Cerebrovascular Constriction Mediated by Hemoglobin

Abstract: Abstract-Although there is evidence that the Rho/Rho kinase pathway and protein kinase C (PKC) are involved in the development of cerebral vasospasm, the mechanism by which subarachnoid hemorrhage (SAH) activates these pathways is unclear. A large body of evidence points to oxyhemoglobin (OxyHb) as a major causative component of blood clot responsible for vasospasm. Therefore, the present studies were conducted to explore whether the Rho/Rho kinase and PKC may be involved in a sustained vasoconstriction induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 39 publications
4
56
1
Order By: Relevance
“…6A, which is published as supporting information on the PNAS web site). A previous study indicated that ␣ and ␤ are the predominant isoforms of PKC expressed in cerebral vascular smooth muscle (23). As expected, CaV1.2 protein was diffusely distributed along the surface membrane of arterial myocytes.…”
Section: Total Internal Reflection Fluorescence Microscopy (Tirf)supporting
confidence: 79%
“…6A, which is published as supporting information on the PNAS web site). A previous study indicated that ␣ and ␤ are the predominant isoforms of PKC expressed in cerebral vascular smooth muscle (23). As expected, CaV1.2 protein was diffusely distributed along the surface membrane of arterial myocytes.…”
Section: Total Internal Reflection Fluorescence Microscopy (Tirf)supporting
confidence: 79%
“…Relatively few studies have examined the functional importance of Rho-kinase in cerebral circulation, but recent evidence suggests that this signaling pathway mediates vasoconstrictor responses to serotonin, endothelin-1, UTP, and oxyhemoglobin (Miao et al, 2002;Nishikawa et al, 2003;Wickman et al, 2003;Luykenaar et al, 2004).…”
Section: Constrictor Responses Of Cerebral Arteries To Angiotensin IImentioning
confidence: 99%
“…Second, we examined the role of Rho-kinase in mediating vasoconstriction in response to Ang II. Activation of Rho-kinase is thought to be a key mechanism of calcium sensitization that mediates responses to several vasoconstrictors (Miao et al, 2002;Nishikawa et al, 2003;Wickman et al, 2003;Luykenaar et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The pathological constriction of cerebral vessels that occurs during CV may lead to ischemia, infarction or death (3,4) and the 3-10 days between the initial hemorrhage and onset of CV potentially affords the clinician a therapeutic window (5). Unfortunately, despite considerable research efforts, the etiology of CV is still unknown, and appears to be a complex combination of events (3,(6)(7)(8)(9)(10) Our research indicates that the intractable vasoconstriction seen in CV after SAH is a combination of a physiological protein kinase C-mediated contraction, followed by a pathological failure to relax, mediated by Rho-mediated inhibition of myosin light chain phosphatase (9,11). Bilirubin oxidation products (BOXes) may be responsible for one or both of these events (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…These increases are reported to be due to mobilization of Rho, which activates rho kinase (ROK). ROK phosphorylates and inactivates MLCP (7,(45)(46)(47). Rho is activated by a number of agonists including thromboxane A 2 and other lipid signaling molecules (48).…”
mentioning
confidence: 99%